Functional TRPV2 and TRPV4 channels in human cardiac c‐kit+ progenitor cells. Issue 6 (10th February 2016) - Che, Hui; Xiao, Guo‐Sheng; Sun, Hai‐Ying; Wang, Yan; Li, Gui‐Rong
Abstract: The cellular physiology and biology of human cardiac c‐kit + progenitor cells has not been extensively characterized and remains an area of active research. This study investigates the functional expression of transient receptor potential vanilloid (TRPV) and possible roles for this ion channel in regulating proliferation and migration of human cardiac c‐kit + progenitor cells. We found that genes coding for TRPV2 and TRPV4 channels and their proteins are significantly expressed in human c‐kit + cardiac stem cells. Probenecid, an activator of TRPV2, induced an increase in intracellular Ca 2+ (Ca 2+ i ), an effect that may be attenuated or abolished by the TRPV2 blocker ruthenium red. The TRPV4 channel activator 4α‐phorbol 12‐13‐dicaprinate induced Ca 2+ i oscillations, which can be inhibited by the TRPV4 blocker RN‐1734. The alteration of Ca 2+ i by probenecid or 4α‐phorbol 12‐13‐dicprinate was dramatically inhibited in cells infected with TRPV2 short hairpin RNA (shRNA) or TRPV4 shRNA. Silencing TRPV2, but not TRPV4, significantly reduced cell proliferation by arresting cells at the G0/G1 boundary of the cell cycle. Cell migration was reduced by silencing TRPV2 or TRPV4. Western blot revealed that silencing TRPV2 decreased expression of cyclin D1, cyclin E, pERK1/2 and pAkt, whereas silencing TRPV4 only reduced pAkt expression. Our results demonstrate for the first time that functional TRPV2 and TRPV4 channels are abundantly expressed in human cardiac c‐kit + progenitor cells. TRPV2 channels, but not TRPV4 channels, participate in regulating cell cycle progression; moreover, both TRPV2 and TRPV4 are involved in migration of human cardiac c‐kit + progenitor cells.